ETIKA PROFESI DAN DASAR MORAL ETIKA TENAGA MEDIS - Naswida, Metha Dian Puspa; Fitri, Sherly Nelsa (Majalah Keadilan, 2020)
The purpose of this writing is to find out what are the professional ethics and ethical moral bases of medical personnel (Medicine). This legal research is included in normative legal research. This research is both perspective and applied. Legal materials in the writing of this study use primary legal materials and secondary legal materials. The legal materials were collected through document study (literature study), using deduction techniques. Professional Ethics for Medical Personnel (Medicine) is regulated in the Indonesian Medical Ethics Code (KODEKI).